ANALISIS SISTEM PENGENDALIAN INTERN PENERIMAAN DAN PENGELUARAN KAS KECIL PADA RUMAH SAKIT UMUM KASIH BUNDA CIMAHI - Hendarwati, Selvy; Dian Candra Fatihah (JEBS (Journal of Economic and Business Student), 2024)
The purpose of this study is to analyse how the internal control system of Kasih Bunda Cimahi General Hospital handles petty cash receipts and expenditures. Weak internal control over cash leads to insecure company assets, and inaccurate information can lead to cash misappropriation and fraud. However, the fact that some companies still exclude the control of petty cash can lead to the possibility of fraud and embezzlement. The subject of the research is Kasih Bunda Cimahi General Hospital. Qualitative research methods were used in this study. The method is carried out through data collection, interviews, documentation and direct field research through observation. The results of the analysis show that the internal control of petty cash income and expenditure at Kasih Bunda Cimahi General Hospital is not fully well run in accordance with the existing theory, there are documents that are not authorised by the authorised official, documents are not fully stamped, cash and staff are not insured. The suggestions that can be given are the completeness of authorisation from the acting authority when issuing cash, making proof of receipt of money from partner banks, and authorising delegation to fill out cheques when the director is not present.